PENINGKATAN KETRAMPILAN PERAWATAN BERKALA MELALUI SIMULASI LOMBA KETRAMPILAN SISWA (LKS) - Aep Surahto; Eko Winarso (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2010)
Technical Junior High School Students majoring in Automotive, doing practicing in authorized workshops such as Suzuki, Toyota, Hyundai, Daihatsu, Mazda and others. The mechanics and supervisors praised about the discipline of the students when working, but the mechanics and supervisors are still confused about working speed and accuracy of work done according to Operation Prochedure Standard (SOP). Advice from some mechanics and supervisors about good teaching in order to be productive must be considered. How should the attitude of teachers for creating the productive students? It is wise to hear the critisism from mechanics and superviseors or other stakeholders. It also become a feedback about what they have done in the school. Have learning materials are delivered in accordance with the needs of students and the community? Are all the potential strongs and abilities of students in the theory and practice produktip been developed to its full potential? Is it true the lack of success was due to errors in selecting methods and learning strategies?